Effects of blood flow restriction therapy for muscular strength, hypertrophy, and endurance in healthy and special populations: a systematic review and meta-analysis - Perera, E.; Zhu, X. M.; Horner, N. S.; Bedi, A; Ayeni, O. R.; Khan, M. (Clinical Journal of Sport Medicine, 2022)
Objectives: Blood flow restriction (BFR) training is an increasingly applied tool with potential benefits in muscular hypertrophy, strength, and endurance. This study investigates the effectiveness of BFR training relative to other forms of training on muscle strength, hypertrophy, and endurance.